2021
DOI: 10.3389/fnhum.2021.749082
|View full text |Cite
|
Sign up to set email alerts
|

Complexity-Based Analysis of the Variations of Brain and Muscle Reactions in Walking and Standing Balance While Receiving Different Perturbations

Abstract: In this article, we evaluated the variations of the brain and muscle activations while subjects are exposed to different perturbations to walking and standing balance. Since EEG and EMG signals have complex structures, we utilized the complexity-based analysis. Specifically, we analyzed the fractal dimension and sample entropy of Electroencephalogram (EEG) and Electromyogram (EMG) signals while subjects walked and stood, and received different perturbations in the form of pulling and rotation (via virtual real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…However, our present results showed that practice under incongruent condition decreased the left TA muscles activity but increased the complexity of left TA sEMG data with higher FD values. This results are consistent with previous studies, where showed that when balance task difficulty increased, the calf muscle activity increased (Gebel et al, 2019) and the complexity of sEMG data decreased (Murillo et al, 2012;Pakniyat and Namazi, 2021). Besides, we also observed that practice under incongruent condition reduced the left MG muscle activity without any significant changes of fractal exponent of left MG muscle (Figure 3).…”
Section: Interpretation Of Complexitysupporting
confidence: 93%
See 3 more Smart Citations
“…However, our present results showed that practice under incongruent condition decreased the left TA muscles activity but increased the complexity of left TA sEMG data with higher FD values. This results are consistent with previous studies, where showed that when balance task difficulty increased, the calf muscle activity increased (Gebel et al, 2019) and the complexity of sEMG data decreased (Murillo et al, 2012;Pakniyat and Namazi, 2021). Besides, we also observed that practice under incongruent condition reduced the left MG muscle activity without any significant changes of fractal exponent of left MG muscle (Figure 3).…”
Section: Interpretation Of Complexitysupporting
confidence: 93%
“…Accordingly, we hypothesized that the complexity of EEG data would decrease after repeated balance practice. Previous studies found that when the difficulty in balance tasks increased, the lower limb muscle activity increased (Gebel et al, 2019) and the complexity of sEMG data from calf muscles decreased (Murillo et al, 2012;Pakniyat and Namazi, 2021). Since these results suggested that higher sEMG complexity probably reflect an effective strategy in postural muscles when facing perturbations, we hypothesized that the complexity of sEMG data of calf muscles would increase after repeated balance practice.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…For this reason, SampEn has been calculated with a smaller number of data points or with using a continuous signal [ 13 ]. Various forms of continuous data [ 2 , 8 , 10 ] have been used in complexity analysis, however, the usage of center of pressure (COP) signal during a steady-state, where many consecutive steps can be captured, is becoming more popular [ 9 , 14 16 ]. The COP at a given moment in time is the location of resultant vertical ground reaction force vector.…”
Section: Introductionmentioning
confidence: 99%